2022
DOI: 10.1111/and.14374
|View full text |Cite
|
Sign up to set email alerts
|

Should haematological inflammatory markers be included as an adjuvant in the differential diagnosis of acute scrotal pathologies?

Abstract: The aim of this study was to determine discriminative role of haematological inflammatories between acute scrotal pathologies and malignancies. In addition, it was aimed to search for a predictive marker of testicular survival in the TT group. Medical data of 141 patients with acute scrotal pathology and 63 TTm patients who presented to our clinic between January 2015 and July 2019 were retrospectively reviewed and compared in terms of haematological values and demographic parameters following the inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…22 Yilmaz et al found that monocyte count was the only significant variable of testicular viability (OR, 0.046; 95% CI, 0.006-0.366; p = 0.004) in patients with testicular torsion using multivariate analysis. 23 The authors noted that the monocyte count in patients with testicular torsion might indicate testicular viability. In our study, monocyte count was identified as an independent risk factor for testicular salvage during testicular torsion using multivariate logistic regression analysis (OR, 0.012; 95% CI, 0.000-0.755; p = 0.036).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Yilmaz et al found that monocyte count was the only significant variable of testicular viability (OR, 0.046; 95% CI, 0.006-0.366; p = 0.004) in patients with testicular torsion using multivariate analysis. 23 The authors noted that the monocyte count in patients with testicular torsion might indicate testicular viability. In our study, monocyte count was identified as an independent risk factor for testicular salvage during testicular torsion using multivariate logistic regression analysis (OR, 0.012; 95% CI, 0.000-0.755; p = 0.036).…”
Section: Resultsmentioning
confidence: 99%
“…Yilmaz et al. found that monocyte count was the only significant variable of testicular viability (OR, 0.046; 95% CI, 0.006–0.366; p = 0.004) in patients with testicular torsion using multivariate analysis 23 . The authors noted that the monocyte count in patients with testicular torsion might indicate testicular viability.…”
Section: Discussionmentioning
confidence: 99%
“…Through multivariate logistic regression analysis, Yilmaz et al observed that monocyte count was the only significant variable of testicular viability in patients with testicular torsion (OR = 0.046, 95%CI: 0.006–0.366, P < 0.004) and that monocyte count could predict testicular salvage in patients with testicular torsion ( 19 ). Merder et al ( 7 ) retrospectively analyzed the data of 88 patients with testicular torsion (61 cases of orchiopexy and 27 cases of orchiectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al. reported that monocyte counts predict testicular preservation, 3 but evidence regarding blood markers is still lacking and controversial.…”
mentioning
confidence: 99%